Reproductive Timing of Erimystax insignis (Blotched Chub) in the Flint River of North Alabama - Bruce Stallsmith; Josh Mann; Candice Allen (Southeastern Fishes Council Proceedings, 2015)
Important details of the reproductive ecology of many freshwater fishes of the species-rich southeastern United States are still poorly known. One such species is Erimystax insignis (Blotched Chub), whose range includes the Tennessee River drainage in northern Alabama, USA. To determine timing and patterns of reproductive effort, collections were made monthly of as many as 30 individuals from August 2011 through July 2012 from a 14 km stretch of the Flint River in Madison County, Alabama. Female and male gonadosomatic index (GSI) and ovarian development data indicate that reproductive activity for the species peaks from March through May. Ripe and mature oocytes were found in females from March through June peaking in April but ripe ovaries were found only in March and April. The number of mature and ripe oocytes was larger than reported for a population in the Little River of Tennessee, and diameter of all stages of maturing oocytes was smaller than the Little River population.
Keywords: GSI; ovarian development; Tennessee River; cyprinid